The Complex Link and Disease Between the Gut Microbiome and the Immune System in Infants - Zhang, Huan; Zhang, Zhilin; Liao, Yiqun; Zhang, Wenjie; Tang, Dong (Frontiers in Cellular and Infection Microbiology, 2022)
The human gut microbiome is important for human health. The development of stable microbial communities in the gastrointestinal tract is closely related to the early growth and development of host immunity. After the birth of a baby, immune cells and the gut microbiome mature in parallel to adapt to the complex gut environment. The gut microbiome is closely linked to the immune system and influences each other. This interaction is associated with various diseases in infants and young children, such as asthma, food allergies, necrotizing colitis, obesity, and inflammatory bowel disease. Thus, the composition of the infant gut microbiome can predict the risk of disease development and progression. At the same time, the composition of the infant gut microbiome can be regulated in many ways and can be used to prevent and treat disease in infants by modulating the composition of the infant gut microbiome. The most important impacts on infant gut microbiota are maternal, including food delivery and feeding. The differences in the gut microbiota of infants reflect the maternal gut microbiota, which in turn reflects the gut microbiota of a given population, which is clinically significant.